Serological evidence of Newcastle disease virus antibodies in wild birds in Zaria, Kaduna State, Nigeria - Inuwa, Bitrus; Yiltawe, Wungak; Shuaib Adamu, Gidado; Oyekan, Olumuyiwa; Osemeke Onyeka, Henry; Ochuko, Orakpoghenor; Gulak Hussaini, Ularamu; Ismailia , Shittu; Meseko, Clement (Veterinaria Italiana, 2023)
Wild birds have been reported to be reservoirs of viral diseases of poultry, and play an epidemiological role in their maintenance and spread. A serological survey was undertaken to determine the evidence of Newcastle disease virus (NDV) antibodies in wild birds in Zaria Kaduna State, Nigeria. A total of 150 apparently healthy wild birds comprising 30 each laughing dove, speckled pigeons, cattle egrets, village weavers and African silver bills were sampled. Sera collected were analysed for the presence of antibodies against NDV and avian paramyxovirus‑2 (APMV‑2) using the haemagglutination inhibition test. The results showed an overall seroprevalence of 4% (95% CI: 2.05‑10.1) to NDV. African silver bill showed a seroprevalence of 10.0% (95% CI: 2.61‑24.9) NDV antibodies while seroprevalence of 3.3% (95% CI: 0.16‑15.4) was recorded for cattle egrets, village weavers and laughing doves respectively. No statistically significant difference existed for NDV seroprevalence (P>0.05) among the different species of wild birds. All the 150 sera tested negative for APMV‑2 antibodies. The result of this study confirmed the exposure of wild birds to NDV in the study area. Continuous surveillance with isolation and characterization of NDV in the wild birds is therefore recommended for strategic planning for control.